(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The understanding of human capital through social-philosophical view is took place in this work. Nowadays there are many explanations of human capital in various spheres of science. The author gives a brief explanation of this meaning. Also the development of human capital in Kazakhstan, particularly of intellectual capital is discussed as the main factors for strengthening national economy. The role of intellectual capital is a key aspect in the development of people productivity. That is why education is admitted as the most important factor of development and strengthening of intellectual potential of science, the guarantor of her independence and international competitiveness today and it is a fundamental condition for implementation by the person of the civil, economic and cultural right. Along with it, it should be noted that the development of cultural capital in Kazakhstan which plays a key role in formation of the human capital and exists as its integral component, is a spiritual wealth of the person in the form of his cultural development as the sets of steady forms of social interaction. Therefore, the spiritual condition of the person in society directly influences its human potential, level of social relationship in society. The aim of this article is to say that people in any country are developed by giving them knowledge, education, good social conditions, but the spiritual condition of person is more important. Because spiritual condition influence on the ability of people to create, to be useful and to be productive for society. Kazakhstan took a new strategic direction for being competitive among developed countries. In this course it is very important to save national identity in the process of globalization and integration. And the national identity with saving cultural capital of Kazakhstan people can help for our country to develop and up bring new smart generation Key words: human capital, cultural capital, intellectual capital.